2003
DOI: 10.1093/ajcn/77.5.1255
|View full text |Cite
|
Sign up to set email alerts
|

Dietary potential renal acid load and renal net acid excretion in healthy, free-living children and adolescents

Abstract: Predicting NAE from dietary intakes, food tables, and anthropometric data is also applicable during growth and yields appropriate estimates even when self-selected diets are consumed. The PRAL estimate based on only 4 nutrients may allow relatively simple assessment of the acidity of foods and diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
293
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(320 citation statements)
references
References 37 publications
7
293
1
6
Order By: Relevance
“…Acid-base balance Net acid excretion (NAE ind ) of the subjects was estimated indirectly from the diet by the method of Remer and Manz (Remer et al, 2003): Sodium and chlorine were not included in the calculation as salt intake was not measured and these elements tend to balance each other. Calcium was also omitted as it has the smallest impact on acid-base balance (Remer et al, 2003). The subjects were grouped in fifths of NAE ind (both sexes combined), in order to examine the other characteristics of their diet for each fifth.…”
Section: Coding and Nutrient Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Acid-base balance Net acid excretion (NAE ind ) of the subjects was estimated indirectly from the diet by the method of Remer and Manz (Remer et al, 2003): Sodium and chlorine were not included in the calculation as salt intake was not measured and these elements tend to balance each other. Calcium was also omitted as it has the smallest impact on acid-base balance (Remer et al, 2003). The subjects were grouped in fifths of NAE ind (both sexes combined), in order to examine the other characteristics of their diet for each fifth.…”
Section: Coding and Nutrient Analysismentioning
confidence: 99%
“…The method of Remer and Manz takes into account the range of nutrients previously described and it adjusts for nutrient absorption and body size (Manz et al, 1984). This method has also been validated against renal net acid excretion in adults and adolescents (Remer & Manz, 1994;Remer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Montenegro-Bethancourt (2013) provided, for the first time, evidence for an association between fruit and vegetables intake and children hydration status. Although other authors (26,27) speculated that fruit and vegetables were an essential predictor of hydration status, we also assessed the association with other food groups such as "milk and dairy products", and "coffee, barley, sodas, juices and water". Nonetheless, our findings revealed that only high "fruit and vegetables" intake was significantly associated with a better hydration status.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of dietary acid load scores and dietary patterns PRAL and NEAP scores were derived from estimations of several nutrient intakes [17] Quartiles of the scores were used for statistical analysis. A second strategy to identify diabetes cases used first information exclusively from the drug reimbursement database (n =1,216 participants, who did not self-report any information on diabetes, and had at least one diabetes drug reimbursed).…”
Section: Assessment Of Dietary Informationmentioning
confidence: 99%